2018
DOI: 10.1186/s12917-018-1647-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of Haemophilus (Glässerella) parasuis serovar 5 subjected to culture conditions partially mimetic to natural infection for the search of new vaccine antigens

Abstract: BackgroundHaemophilus (Glässerella) parasuis is the etiological agent of Glässer’s disease in pigs. Control of this disorder has been traditionally based on bacterins. The search for alternative vaccines has focused mainly on the study of outer membrane proteins. This study investigates the transcriptome of H. (G.) parasuis serovar 5 subjected to in vitro conditions mimicking to those existing during an infection (high temperature and iron-restriction), with the aim of detecting the overexpression of genes cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The identification and quantification of differentially expressed genes (DEGs) can be conducted at a transcriptomic level by using RNA sequencing (RNA-seq) technology. This transcriptomic approach has identified 13 upregulated genes encoding for proteins exposed to iron-restriction stress at the bacterial surface of Hemeophilus ( Glässerella ) parasuis ( Alvarez-Estrada et al, 2018 ). In addition, RNA-seq can also be used to characterize sRNAs, including their secondary structure and predicted mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…The identification and quantification of differentially expressed genes (DEGs) can be conducted at a transcriptomic level by using RNA sequencing (RNA-seq) technology. This transcriptomic approach has identified 13 upregulated genes encoding for proteins exposed to iron-restriction stress at the bacterial surface of Hemeophilus ( Glässerella ) parasuis ( Alvarez-Estrada et al, 2018 ). In addition, RNA-seq can also be used to characterize sRNAs, including their secondary structure and predicted mRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the crp gene promotes the uptake of iron from the host by regulating the expression of genes involved in iron uptake. Therefore, we measured the expression of tbpA, tbpB, and cirA, each related to iron uptake (Álvarez-Estrada et al, 2018), by real-time PCR. The results indicated that the expression of tbpA, tbpB, and cirA in the crp mutant were significantly reduced compared with the wild type ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the hxuCBA operon is upregulated in iron–heme restricted medium in a Fur‐dependent manner (Harrison et al, 2013; Whitby et al, 2006). In H. parasuis serovar 5, the hxuCBA operon is upregulated in vitro in conditions mimicking infection with iron limitation and higher temperature (Alvarez‐Estrada et al, 2018). Recently, as mentioned above for the Hmw adhesins and other outer membrane proteins, the expression of the hxuCBA operon was found to be biphasic due to ModA (Atack et al, 2015).…”
Section: The Regulation Of Hemopexin‐binding Proteinsmentioning
confidence: 99%